PELATIHAN PENGOLAHAN “PAYA BITES”, CEMILAN SEHAT BERBAHAN PEPAYA, BAGI ANGGOTA FKIF UNNES - Na’im, Muhammad Rizqu Zidan; Aulia, Akhisna Citra; Mariska, Mela; Kamilia, Habibah Nurul; Husna, Alifah Fiani Salwa (Jurnal Pengabdian dan Kewirausahaan, 2024)
Papaya is a seasonal fruit that is rich in water content and has a relatively short shelf life. Nowadays, people's interest in consuming fruit directly after it is ripe is relatively low because some of them don't like fruit. For this reason, it is necessary to innovate fruit-based products, as an effort to overcome the problem of lack of fruit consumption. This article discusses "PAYA BITES", an entrepreneurial venture that presents papaya crackers as an innovative snack product made from papaya with a variety of contemporary flavors. In this activity, the method used was training (socialization) aimed at 41 members of the Islamic Physics Study Forum (FKIF) at Semarang State University. This activity aims to be a form of education and training for FKIF UNNES members in processing papaya fruit into papaya crackers and has the potential to be marketed to the general public. The result of this training is to provide knowledge and convenience for FKIF UNNES members in processing papaya fruit into papaya crackers which have so far been underutilized so that they become a more valuable commodity